TATA CARA GANTI KERUGIAN DALAM PENGADAAN TANAH UNTUK PEMBANGUNAN JALAN TOL DI SICINCIN TERHADAP TANAH PUSAKO TINGGI (STUDI KASUS KORONG LADANG LAWEH NAGARI SICINCIN KECAMATAN 2X11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN) - Firmaneti, Putri; Syuryani, Syuryani; Adriaman, Mahlil (Ensiklopedia of Journal, 2024)
Compensation is a proper and fair compensation for the party entitled to the land acquisition process. In Korong Ladang Laweh Nagari Sicincin, a lot of land is used for the construction of the Padang-Pekanbaru oll Road. In the procurement of land, there was a dispute because the land was high pusako land. At the time of compensation, many of the distributions were unequal and not in accordance with the results of the natural wealth in the land. Based on the background above, the purpose and usefulness of this writing is to find out the settlement of compensation and the obstacles to completing compensation for land acquisition for people affected by the toll road, while the use of this writing for theoretical use is used as a reference for various parties for the development of knowledge and understanding of compensation and its practical use is beneficial to the community and institutions in compensation for road land acquisition and provides insight into academic and civil law aspects. The method used is the field method through interviews with sources related to this writing. Besides that, using normative methods or secondary data libraries can be found in libraries and the internet. Completion of compensation for pusako high land for the construction of the Toll Road in Korong Ladang Laweh requires prior objection from the land owner, re-identification in the field, and showing proof of land ownership and documents that have been signed or agreed upon, if not resolved in the family then pursued by means of legal channels. The obstacles in the settlement of compensation for the procurement of pusako tinggi land for the construction of the Padang-Pekanbaru Toll Road are due to the minimal education of the people, the lack of community participation, the existence of fraud, namely the unequal distribution of one ranji, and violations of agreements with the ninik mamak of their people. Therefore, this can hinder the settlement of cases against high pusako tinggi .Keywords: compensation, land, pusako tinggi.